Encyclopaedia of physical education and sports Vol.14 Spirit of sports - Mudgal, Rahul (Ed); Sharma, Bela Rani (ed); Kaushik, Vijaya (Ed.) (New Delhi Sarup Book Publishers, 2012)
Variety of religious experience